New evidence about the subduction of the Copiapó ridge beneath South America, and its connection with the Chilean-Pampean flat slab, tracked by satellite GOCE and EGM2008 models. (November 2015) - Álvarez, Orlando; Gimenez, Mario; Folguera, Andres; Spagnotto, Silvana; Bustos, Emilce; Baez, Walter; Braitenberg, Carla
Highlights: Vertical gravity gradient show a deflection of the main Andean structures trend. Relationship between the Copiapo ridge and deformation in the upper plate. The Copiapo ridge controls the northern edge of the Chilean flat subduction zone. Leading to shallower subduction at the northern region of the Chilean flat-slab. Chilean-Pampean flat slab could be related to two simultaneous ridge collision. Abstract: Satellite-only gravity measurements and those integrated with terrestrial observations provide global gravity field models of unprecedented precision and spatial resolution, allowing the analysis of the lithospheric structure. We used the model EGM2008 (Earth Gravitational Model) to calculate the gravity anomaly and the vertical gravity gradient in the South Central Andes region, correcting these quantities by the topographic effect. Both quantities show a spatial relationship between the projected subduction of the Copiapó aseismic ridge (located at about 27°–30° S), its potential deformational effects in the overriding plate, and the Ojos del Salado-San Buenaventura volcanic lineament. This volcanic lineament constitutes a projection of the volcanic arc toward the retroarc zone, whose origin and development were not clearly understood. The analysis of the gravity anomalies, at the extrapolated zone of the Copiapó ridge beneath the continent, shows a change in the general NNE-trend of the Andean structures to an ENE-direction coincident with the area of the Ojos del Salado-San Buenaventura volcanic lineament. This anomalous pattern over the upper plate is interpreted to be linked with the subduction of the Copiapó ridge. We explore the relation between deformational effects and volcanism at the northern Chilean-Pampean flat slab and the collision of the Copiapó ridge, on the basis of the Moho geometry and elastic thicknesses calculated from the new satellite GOCE data. Neotectonic deformations interpreted in previous works associated with volcanic eruptions along the Ojos del Salado-San Buenaventura volcanic lineament is interpreted as caused by crustal doming, imprinted by the subduction of the Copiapó ridge, evidenced by crustal thickening at the sites of ridge inception along the trench. Finally, we propose that the Copiapó ridge could have controlled the northern edge of the Chilean-Pampean flat slab, due to higher buoyancy, similarly to the control that the Juan Fernandez ridge exerts in the geometry of the flat slab further south.